Comparison of early and on-demand maternal feeding after Caesarean delivery: a prospective randomised trial - Ozbasli, Esra; Takmaz, Ozguc; Dede, Faruk Suat; Gungor, Mete (SINGAPORE MEDICAL ASSOC, 2021)
INTRODUCTION This study aimed to compare early and on-demand maternal feeding after Caesarean delivery in terms of gastrointestinal complaints and patient satisfaction. METHODS A total of 262 women with uncomplicated singleton term pregnancies who underwent a Caesarean section under regional anaesthesia were randomised to a soft food diet served at Postoperative Hour 2 (early feeding group) or eating whenever they wanted to upon return to the ward (on-demand group). Patient satisfaction scores at the time of discharge and gastrointestinal complaints were compared. RESULTS The fed-early group comprised 133 (50.8\%) women and the on-demand group comprised 129 (49.2\%) women. Major characteristics and surgical procedures were comparable between the two groups. No significant between-group differences in demographic criteria or surgical procedures were evident (p > 0.05). The mean time to the first feeding was 120.00 +/- 00.00 minutes for the early feeding group as compared to 236.59 +/- 107.74 minutes for the on-demand feeding group (p = 0.001). Satisfaction levels did not differ significantly between the two groups (p = 0.366). Duration to first breastfeeding, analgesia on the ward, passage of flatus, defecation, mobilisation and urination after catheter removal did not differ significantly between the two groups (p > 0.05). CONCLUSION Early initiation of solid food in low-risk women after Caesarean delivery under regional anaesthesia was associated with high satisfaction and did not increase gastrointestinal complaints. We suggest having
Keywords: Caesarean delivery; gastrointestinal complaints; patient satisfaction; postoperative feeding; prospective randomised trial